Application of 5s Culture in Mathematics for the Islamic Character Building in Elementary School Students - Samsul Bahri; Nurul Akmal; Eri Saputra (SAINTIS Publishing, 2022)
This study aims to find out: 1) What Islamic character values are instilled in students of SDN 3 Nisam. 2) The process of implementing the Islamic character building of students through the application of 5S culture to mathematics lessons in SDN 3 Nisam. The type of research is qualitative descriptive with sampling techniques are: observational data, interviews, and documentation. The results are: 1) Islamic character values for elementary school students are instilled in students, namely: religious, honest, social and environmental caring attitude, cleanliness, discipline, hard work, nationalism, respecting achievement, peace-loving, friendly, and fond of reading and counting, 2) Implementation of Islamic character building for elementary school students: a) Formulating Islamic character into math subjects in primary school, b) Cultivate students' habits of good manners through 5S culture, c) Giving appreciation to students who are have good character, d) The Teacher becomes an example in the formation of Islamic character.